A Scoping Study of Insomnia Symptoms in School Teachers. Issue 3 (4th May 2023) - Gierc, Madelaine; Jackowich, Robyn A.; Halliday, Sandra; Davidson, Judith R.
ABSTRACT: Objectives: Although the demands and stress of teaching are generally recognized, little is known about the prevalence and nature of insomnia symptoms in teachers. This scoping study investigated the following questions: How prevalent are insomnia symptoms in teachers? What biopsychosocial variables are associated with insomnia symptoms in teachers? What, if any, interventions for insomnia symptoms in teachers have been studied? Method: We searched Medline, PsycINFO, Embase, CINAHL, Education Source, and ERIC for original peer-reviewed research on school teachers (kindergarten through high school) and insomnia symptoms (self-reported trouble falling or staying asleep). Results: We identified 33 relevant articles from 15 countries. The literature was heterogeneous and generally of low quality with respect to the measurement of insomnia. Based on studies that met validity and reliability criteria, 36–61% of teachers reported insomnia symptoms. Associated factors included: being female, classroom violence, low job satisfaction, pain, depression, and rumination. One online intervention, which included stimulus control, sleep restriction, and techniques for reducing rumination, provided evidence of efficacy. Conclusion: Despite the importance of teachers and their work, high-quality research on insomnia in teachers is lacking. Research in this area is sorely needed. Studies should investigate insomnia symptoms over the school year, identify antecedents of insomnia, and develop interventions with the ultimate goals of understanding, preventing, and treating insomnia symptoms in teachers.